Evidence for the existence and potential roles of intra-islet glucagon-like peptide-1. Issue 1 (4th March 2021) - Campbell, Scott A.; Johnson, Janyne; Light, Peter E.
ABSTRACT: Glucagon-Like Peptide-1 (GLP-1) is an important peptide hormone secreted by L-cells in the gastrointestinal tract in response to nutrients. It is produced by the differential cleavage of the proglucagon peptide. GLP-1 elicits a wide variety of physiological responses in many tissues that contribute to metabolic homeostasis. For these reasons, therapies designed to either increase endogenous GLP-1 levels or introduce exogenous peptide mimetics are now widely used in the management of diabetes. In addition to GLP-1 production from L-cells, recent reports suggest that pancreatic islet alpha cells may also synthesize and secrete GLP-1. Intra-islet GLP-1 may therefore play an unappreciated role in islet health and glucose regulation, suggesting a potential functional paracrine role for islet-derived GLP-1. In this review, we assess the current literature from an islet-centric point-of-view to better understand the production, degradation, and actions of GLP-1 within the endocrine pancreas in rodents and humans. The relevance of intra-islet GLP-1 in human physiology is discussed regarding the potential role of intra-islet GLP-1 in islet health and dysfunction.